BENTUK LARANGAN JURAI SEBAGAI PRANATA MASYARAKAT DI MUARA SAHUNG, KABUPATEN KAUR, BENGKULU - Dhanurseto Hadiprashada Hadiprashada,; Budi Guntoro,; Mudiyono Mudiyono; Subejo Subejo (Universitas Gadjah Mada, 2016)
The value of cultural wisdom that exist in the society in Kaur District, Bengkulu Province, could beapplied in the form of verbal message. They believe that verbal messages, which are used, are convincedby community as a heritage that could become a social regulation. The lack of communication betweengovernment and the community becomes the factor in implementing these values. The lack of attentionfrom the government put culture seemed to be an obstacle factor in development. Documenting thelocal knowledge of community related to cultural values became a problem in contributing to thedevelopment. This verbal messages are called as larangan jurai and used by the community in the NapalHijau village, Muara Sahung, Kaur District, Bengkulu Province. Larangan jurai contains regulations tocommunicate with each other, culture, and the Creator. This study gives an overview about manners,habits, behaviours, and customs as social regulations in the community. The community believed thatlarangan jurai could be able to give the contribution of development in various fields.